Emotion Dysregulation and Psychological Distress in Students - Dastagir, Moafia; Khan, Muhammad Rashid; Israr, Raazia (Journal of Peace, Development and Communication, 2021)
The given study found relationship between Emotion Dysregulation and Psychological Distress in students. Correlation research design was used to explore the results of 400 students of age ranges 15-25, (male=200, female=200) from different educational institutes of Lahore. Difficulties in Emotion Regulation Scale (DERS; Gratz& Roemer, 2004) and Kessler’s scale of Psychological Distress (Kessler, 2002) was used to found dysregulated emotionsand psychological issues respectively. Analysis were conducted to find relationship between Emotion Dysregulation and Psychological Distress as well predicting role of Emotions for outcome variable Psychological Distress. Result showed significant relationship between Emotion Dysregulation and Psychological Distress.Moreover, result showed Emotion Dysregulation positively predicted Psychological Distress. On the basis of this information future Mental Health related programs and advanced intervention plans would be introduced at educational institutes to reduce distress due to dysregulated/maladaptive emotions.